Accidents caused by kerosene lamps: New evidence from African household data - Luciane Lenz; Laura Montenbruck; Maximiliane Sievert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
The use of kerosene for lighting, cooking, and heating in developing countries is often considered a major health threat as it can cause accidents like thermal injuries, poisonings, fires or explosions. A number of hospital surveys emphasize this threat but evidence from household data is extremely scarce and mostly outdated. The present paper is one of the first to investigate the link between kerosene-based lighting and accidents at the household level. We use survey data from 3,326 non-electrified households in Burkina Faso, Rwanda, Senegal, and Zambia and observe very heterogeneous kerosene lamp usage rates. In some regions, accidents with kerosene lamps occur in a substantial share of the population, but the absolute incidence is rather low. – – Das Beleuchten, Kochen und Heizen mit Kerosin wird in Entwicklungsländern oftmals aufgrund von Unfällen wie Verbrennungen, Vergiftungen oder Explosionen als eine wichtige Gefahrenquelle angesehen. Die Wichtigkeit des Problems wird durch einige Krankenhausstudien belegt, Evidenz aus Haushaltsdaten ist jedoch gering und zumeist veraltet. Dieses Papier betrachtet den Zusammenhang zwischen kerosin-basierter Beleuchtung und Unfällen auf Haushaltsebene. Wir nutzen hierzu Befragungsdaten aus 3,326 nicht-elektrifizierten Haushalten in Burkina Faso, Ruanda, Senegal und Sambia und beobachten sehr heterogene Nutzung von Kerosinlampen. Unsere Ergebnisse zeigen, dass in manchen Gegenden ein wesentlicher Bevölkerungsteil Unfällen ausgesetzt ist. Das absolute Unfallvorkommen ist allerdings gering.
Keywords: I15; K32; O13; 330; burns; thermal injury; kerosene lamp; traditional lighting; Sub-Sahara Africa